2003
DOI: 10.1002/pssa.200306495
|View full text |Cite
|
Sign up to set email alerts
|

Etching of porous silicon in basic solution

Abstract: This study reveals that a silicon sample with a porous layer immersed in strong basic solution is etched in several steps according to the surface area of the various materials to be dissolved (nano/macroporous or bulk silicon). As a result it demonstrates the possibility to produce various silicon surface morphologies. These morphologies range from macropore structure to inverted pyramids with crystalline facets. The technique used was the immersion of porous silicon in basic solution and the parameters varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…They considered that the framework in the skeleton structure must correspond to the pore walls of macroporous structure. Moreover when high current density was applied, such structure was not observed (9). This result also corresponds to the observation by Vyatkin et al: the pore wall thickness changes with increasing current density (10).…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…They considered that the framework in the skeleton structure must correspond to the pore walls of macroporous structure. Moreover when high current density was applied, such structure was not observed (9). This result also corresponds to the observation by Vyatkin et al: the pore wall thickness changes with increasing current density (10).…”
Section: Introductionsupporting
confidence: 92%
“…The skeleton structure should be an important key to think of this surface dissolution. In this study, when a skeleton structure is observed, a uniform microporous structure is confirmed above the skeleton structure as Hamm et al reported (9). Wehrspohn et al and Ponomarev et al also observed such a uniform microporous layer even on the macroporous layer in their works (13,14).…”
Section: Effect Of Organic Solventsupporting
confidence: 86%
See 2 more Smart Citations
“…Tinsley-Bown and co-workers (Tinsley-Bown et al 2000) described a method based on immersing the porous layers in an ethanol-rich alkali (KOH) solution, whose effect on the pores' diameter may be controlled by the immersion time. Hamm and coworkers (Hamm et al 2003) used a similar method by immersing the PSi samples in a NaOH etching (0.1 and 1 M) solution. To avoid problems due the hydrophobic nature of the PSi walls, an ethanol drop is put on the samples' surface before the immersion in the NaOH solution.…”
Section: Psi Layers Morphology and Designmentioning
confidence: 99%